Wives, Daughters and Sisters: Noble Women in Medieval Lithuania (13th–15th Centuries) - Petrauskas, Rimvydas (Vilnius University Open Series, 2024)
The history of medieval women in Lithuania a little-known topic. This is due to two reasons. Firstly, the long-dominant research tradition, which has given the main role to the history of “great men”, has undoubtedly left women on the margins of studies. Secondly, the state of research has been, and continues to be, largely determined by the availability of the sources. Of all the rulers of Lithuania during the pagan period, only the names of Mindaugas’ wife and both of Algirdas’ wives are known with certainty. Sensing this gap, some of the rulers’ wives were “given” names by later chroniclers. The situation concerning the sources regarding the wives and daughters of the nobility is similar. For example, of the 26 most influential nobles of the time of Grand Duke Vytautas, in 14 cases, we do not know the name or origin of the wife. Nevertheless, the processing and compilation of the rather scattered material on the Lithuanian noble women allows us to draw some conclusions about the political and social system of the Lithuanian medieval state. Women played an important role in the world of the nobility. As wives, daughters, and sisters, they established and maintained ties between relatives, both at home and (in the case of rulers) abroad. Successful marriages often determined the trajectories of men’s careers, and sometimes even of individual families. However, they mostly remained in the silence of the sources and, thanks to the conjuncture of the sources, they appear before us first of all as pious foundresses, preservers of the memory of the family, and guardians of children.